Grant For Cancer Research - Five researchers get RM150 000 to conduct study in the field of oncology - The Star, (2008)
THE National Cancer Council (Makna) has allocated RMISO QOO to five local researchers in the field of oncology the study and research of cancer marking yet another milestone for. Makna in its mission to advance cancer treatment and research in Malaysia.